Cerdas dan Bijak menggunakan Internet di Era Digitalisasi - Lia Khamidatul Aufa (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
This outreach activity aims to provide guidance to underage children regarding the smart and wise use of the Internet at MI Ainul Huda, Sendangharjo Village, Ngasem District, Bojonegoro Regency. The methods used in this activity include material presentation, pre-test questionnaires, and post-test questionnaires. The outreach activity was conducted over one day, on Saturday, May 17, 2025, targeting 4th and 5th-grade MI students. The material covered includes the definition of the Internet, the meaning of Digital Literacy, Internet Ethics, Internet utilization, personal data security tips, and challenges in the digital era along with ways to overcome those challenges.The results of the activity show that this outreach is highly relevant to the current conditions of underage students. This activity had a positive impact and increased the knowledge and understanding of the students, with 90% of them gaining comprehension about the Internet in the digital age.